Estado del arte del tratamiento primario de aguas residuales mejorado químicamente - TPMQ (2016)
This document gathers the progress and historical facts of fifteen (15) cases of waste treatment plants that include in their technology the Chemically Improved Primary Treatment (TPPT) in different parts of the world. Within the analyzes, the reported removal efficiencies of Total Suspended Solids, Biochemical Oxygen Demand and Chemical Oxygen Demand are presented, resulting from the implementation of the TPQM and the overall applicability of the type of treatment.